Leaders' Relational Energy and Employee Job Outcomes: A Moderated Mediation Model Across Three Countries - Roche M; Haar J; Brougham D (John Wiley and Sons Australia, Ltd., 2026)
Our paper challenges current understanding of the importance of relational leadership by demonstrating how the relational energy of leaders influences employee job satisfaction, career satisfaction, and OCBs across three countries. Our overall sample was n = 1277 and comprised employees from New Zealand (n = 427), Australia (n = 401), and the United States (n = 449). We found that leaders' relational energy across three countries (the United States, New Zealand, and Australia) was positively related to followers' work-life balance, job and career satisfaction, and OCBs. Overall, the moderated mediation model highlighted that the work-life balance of employees mediated the relationship between their outcomes and their leaders' relational energy at least partially. Ultimately, we suggest that when leaders create positive relationships with followers by engaging in emotionally energetic and uplifting interactions, positive outcomes for employee wellbeing ensue and we provide empirical evidence of this relationship.